Modeling, Simulation, and Analysis of Novel Threshold Voltage Definition for Nano-MOSFET - Yashu Swami; Sanjeev Rai (Journal of Nanotechnology)
Threshold voltage (VTH) is the indispensable vital parameter in MOSFET designing, modeling, and operation. Diverse expounds and extraction methods exist to model the on-off transition characteristics of the device. The governing gauge for efficient threshold voltage definition and extraction method can be itemized as clarity, simplicity, precision, and stability throughout the operating conditions and technology node. The outcomes of extraction methods diverge from the exact values due to various short-channel effects (SCEs) and nonidealities present in the device. A new approach to define and extract the real value of VTH of MOSFET is proposed in the manuscript. The subsequent novel enhanced SCE-independent VTH extraction method named “hybrid extrapolation VTH extraction method” (HEEM) is elaborated, modeled, and compared with few prevalent MOSFET threshold voltage extraction methods for validation of the results. All the results are verified by extensive 2D TCAD simulation and confirmed analytically at various technology nodes.